Do crystalline water proofing admixtures affect restrained plastic shrinkage behavior of concrete? - Gupta, R.; Biparva, A. (Revista ALCONPAT, 2017)
This paper describes the effect of crystalline water proofing admixtures on early-age cracking in concrete. The performance of three different types of these admixtures was compared to that of control. This study has been performed in two stages. Stage one was performed under ASTM specified conditions and a modified stage where more severe drying conditions than that described in the ASTM test standard were used. These modified conditions simulated inadequate curing under extreme exposure conditions as experienced by concrete in many parts of the world.  The test results indicate that the water proofing admixtures can effectively reduce the early-age shrinkage cracking.  The possible reasons for this secondary advantage of crystalline water proofing admixture is also hypothesized in this paper.